Philosophical basics of ecology and economy - Faber, Malte; Manstetten, Reiner (Routledge studies in ecological economics, 2010)
The distinctive characteristic of this book's approach is to provide a brand new and comprehensive view on problems pertaining to the relationship between humans and nature, without limit to any one particular discipline. Environmental issues are not exclusively physical, biological, economical, political, social, or cultural problems. They are rather all these and more